Analisis Pengaruh Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan Terhadap Kepuasan Pengguna dan Manfaat Bersih Sistem Electronic Document (E-Docs) Pada Life Insurance - Pattipeilohy, William Frado; Priyatna, Ade; Sanwani, Sanwani (TIN: Terapan Informatika Nusantara, 2021)
The Statista.com site predicts that in 2024 the volume of data and information will continue to increase, increasing 75 times compared to data 2010. PT AXA Financial Indonesia is one of the life insurance industries that continues to grow rapidly with an increase in data per day, even though the world is currently experiencing a viral pandemic. Therefore, data storage and documents need to be managed properly. Electronic Document System (e-docs) is a solution for storing data and documents electronically and efficiently. Therefore, it is important to measure the implementation of the Electronic Document System (e-docs). This study aims to determine the effect of System Quality, Information Quality, Service Quality on User Satisfaction and Net Benefits at PT AXA Financial Indonesia. The research method used is quantitative. Data collection was carried out using a questionnaire. Analysis of research data using the Statistical Product and Service Solutions (SPSS) program version 20. The results of this study indicate that the variables of System Quality, Information Quality, Service Quality have a positive and significant effect partially and simultaneously on user satisfaction as well as user satisfaction. partially to the net benefits. Meanwhile, System Quality, Information Quality and User Satisfaction have a positive and significant effect simultaneously on net benefits but do not have a positive effect on Service Quality.